THE PERSONALITY OF HRYHORII SKOVORODA IN THE NARRATIVES OF OLES HONCHAR: PSYCHOLINGUISTIC DIMENSIONS - Іhnatieva, Svitlana; Tsiupiak, Iryna (European Science, 2023)
The essential aspects of the personality of Hryhorii Skovoroda in the diary narrative of Oles Gonchar in the psycholinguistic dimensions context are studied. The entire corpus of diary entries is considered as a narrative model existing in space and time.